An improved quasi-Newton equation on the quasi-Newton methods for unconstrained optimizations - Basim Abbas Hassan; Kanikar Muangchoo; Fadhil Alfarag; Abdulkarim Hassan Ibrahim; Auwal Bala Abubakar (Institute of Advanced Engineering and Science, 2021)
Quasi-Newton methods are a class of numerical methods for solving the problem of unconstrained optimization. To improve the overall efficiency of resulting algorithms, we use the quasi-Newton methods which is interesting for quasi-Newton equation. In this manuscript, we present a modified BFGS update formula based on the new quasi-Newton equation, which give a new search direction for solving unconstrained optimizations proplems. We analyse the convergence rate of quasi-Newton method under some mild condition. Numerical experiments are conducted to demonstrate the efficiency of new methods using some test problems. The results indicates that the proposed method is competitive compared to the BFGS methods as it yielded fewer iteration and fewer function evaluations.